Synthesis of 1-(2-(4-substitutedphenylamino)-imidazo[2,1-b] benzoxazol-3-yl) ethanone (Global Journal of Science Frontier Research, 2014)
4-acetyl-3-(4-substitutedphenylamino)-isoxazole-5(2H)-one, substituted on nitrogen with a 2-chlorobenzo[d] oxazole group, reacts with triethylamine (TEA) in ethanol under reflux conditions to provide a convenient synthesis of 1-(2-(4-substitutedphenylamino)-imidazo-[2,1-b]benzoxazol-3-yl)-ethanone.
Keywords: isoxazolones; 2chlorobenzo[d]oxazole; Imidazobenzoxazol; Baseinducedrearrangements